Hệ GT90 – một hệ quản trị cơ sở dữ liệu khai thác theo thời gian thực - Mạnh, Lê (Journal of Computer Science and Cybernetics, 2016)
The article presents system software management data bank  of directory telephone Hochiminh city. This system can be managing about 30000 subcrible. This kind of  this system efficient in the most city